Populism in the Self Presentation of Politician on Ganjar Pranowo's Instagram Account - Kirana Ayudifa; Rona Rizkhy Bunga Chasana (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2023)
ABSTRACT As one of the most popular social media in Indonesia, Instagram is widely used by political actors to present themselves to attract the potential voters. Ganjar Pranowo, who’s often referred as a populist politician, has been widely discussed as a candidate for the 2024 presidential election. This research wants to analyze the self-presentation form of Ganjar Pranowo's populism communication on Instagram. A qualitative content analysis methods are used to analyze the visual content in the form of videos from Ganjar Pranowo's Instagram posts. With purposive sampling, 5 samples were obtained which would be analyzed. The results of the analysis show that on Instagram, Ganjar Pranowo plays himself as a political actor who’s close to the citizens, friendly, firm, empathetic, and loves his family. Based on the self-presentation shown, it’s known that Ganjar Pranowo displayed two of the three most common characteristics of populism according to Jager and Walgrave through his Instagram account during the research period, which is referring to the people and exclusion of outside groups. These findings indicate that there is a tendency for political bias and identity politics in Ganjar Pranowo's self-presentation of populism on Instagram that shown through the behavior of referring to certain groups of people. Populism behavior shown by politicians on social media is known to be able to influence the climate of Indonesian political communication in the modern era.ABSTRAK Sebagai salah satu media sosial paling populer di Indonesia, Instagram banyak dimanfaatkan para aktor politik untuk mempresentasikan diri mereka sebagai cara menarik perhatian calon pemilih. Ganjar Pranowo yang sering disebut sebagai politisi populis yang dekat dengan rakyat saat ini banyak dikaitkan dengan kabar pencalonannya di Pemilihan Presiden 2024 mendatang. Penelitian ini ingin menganalisis bentuk presentasi diri komunikasi populisme Ganjar Pranowo di Instagram. Metode analisis isi kualitatif digunakan untuk menganalisis konten visual berupa video dari postingan Instagram Ganjar Pranowo. Dengan purposive sampling, didapat 5 sampel yang akan dianalisis. Hasil analisis menunjukkan bahwa di Instagram, Ganjar Pranowo memerankan dirinya sebagai aktor politik yang merakyat, supel, tegas, empatis, dan sayang keluarga. Berdasarkan presentasi diri yang ditunjukkan, didapatkan bahwa Ganjar Pranowo menampilkan dua dari tiga ciri populisme paling umum menurut Jager dan Walgrave melalui akun Instagramnya selama kurun waktu penelitian, yaitu merujuk kepada rakyat dan pengecualian terhadap kelompok luar. Temuan ini mengindikasikan adanya kecenderungan bias politik dan politik identitas pada presentasi diri populisme Ganjar Pranowo di Instagram yang ditunjukkan melalui perilaku perujukan kepada kelompok masyarakat tertentu. Perilaku populisme yang ditunjukkan politisi di media sosial diketahui mampu mempengaruhi iklim komunikasi politik Indonesia di era modern.